Teknologi Game untuk Pembelajaran bagi Anak dengan ADHD: Tinjauan Literatur - Rahadian Kurniawan; Raden Bagoes Yudha Rangga Sanjaya; Restu Rakhmawati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
The use of game technology in the learning domain for children with Attention Deficit Hyperactivity Disorder (ADHD) has begun to emerge. Until recently, many studies have been conducted to prove game technology usage’s effectiveness in the learning process for children with ADHD. This paper is a systematic literature review aimed to map the use of game technology in the learning process for children with ADHD and identify a future research roadmap. Based on the exploration of the literature obtained by applying the inclusion criteria, 30 primary studies were selected. The analysis yielded a mapping of game technology goals, game technology genres, game technology platforms, and game technology testing. The literature review results indicate that the use of game technology to improve attention in children with ADHD is proven to be relevant and can be the right choice to enhance the focus skills and learning processes. In addition, this literature review identified three roadmaps for future research, namely paying more attention to other ADHD’s comorbidities as the future research’s goal, paying more attention to variations in the respondents’ background involved in the learning game design process, and using other platforms as media for future learning.